2013
DOI: 10.1371/journal.pone.0058631
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Secretory Protein of 94 Amino Acids (PSP94) Binds to Prostatic Acid Phosphatase (PAP) in Human Seminal Plasma

Abstract: Prostate Secretory Protein of 94 amino acids (PSP94) is one of the major proteins present in the human seminal plasma. Though several functions have been predicted for this protein, its exact role either in sperm function or in prostate pathophysiology has not been clearly defined. Attempts to understand the mechanism of action of PSP94 has led to the search for its probable binding partners. This has resulted in the identification of PSP94 binding proteins in plasma and seminal plasma from human. During the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Interestingly, human CRISP3 and CRISP2 share 71.4% sequence identity. Earlier studies from our lab have demonstrated the ability of CRISP3 from human seminal plasma to bind to PSP94 using affinity chromatography . In this direction, we also identified CRISP2 as one of the probable binding proteins from human sperm.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Interestingly, human CRISP3 and CRISP2 share 71.4% sequence identity. Earlier studies from our lab have demonstrated the ability of CRISP3 from human seminal plasma to bind to PSP94 using affinity chromatography . In this direction, we also identified CRISP2 as one of the probable binding proteins from human sperm.…”
Section: Introductionsupporting
confidence: 69%
“…Human CRISP3 is a glycosylated protein secreted mainly by the prostate and has been demonstrated to interact with prostate secretory protein of 94 amino acids (PSP94) in human seminal plasma . Previous reports have shown PSP94‐binding protein (PSPBP) from human serum to interact with PSP94 , as CRISP3 and PSPBP are only structurally related in the CAP domain.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have shown CRISP-3 to be interacting with PSP94 in human seminal plasma (122)(123)(124). Unlike PSP94, CRISP-3 expression is upregulated during prostate tumorigenesis and both have been considered for diagnosis and prognosis of PCa (88).…”
Section: Cysteine Rich Secretory Protein (Crisp)mentioning
confidence: 99%
“…Total RNA was prepared from 0.5 g of G. blomhoffii brevicaudus liver, using Sepasol ® -RNA I Super (Nacalai Tesque, Kyoto, Japan) according to the manufacturer's instructions, and this RNA was then reverse-transcribed to prepare the first cDNA strand by using an adaptor-linked oligo(dT) primer [5′-GGCCACGCGTCGACTAGTAC-(dT) 17 -3′]. The resulting cDNAs were further amplified by PCR by using an ssp-sigN specific primer [5′-CCCTAC-CAAGAGTTTCCTGGGTCTTCN-3′, corresponding to the 5′-untranslated region (UTR) of hSSP] and a 3′-Adp adaptor primer (5′-GGCCACGCGTCGACTAG-TAC-3′, corresponding to the adaptor sequence).…”
Section: Electrophoresismentioning
confidence: 99%
“…Although the biological function of PSP94 has not been unequivocally established, it has the ability to bind a protein in human blood (the PSP94-binding protein) and cysteine-rich secretory protein-3 (CRISP-3) from human leukocytes. 15,16) Anklesaria et al 17) have recently shown prostatic acid phosphatase to be another binding protein for PSP94 and proved the presence of the acid phosphatase-PSP94 complex in human seminal plasma.…”
mentioning
confidence: 99%